Firm evidence of complete revascularization with culprit and target vessel revascularization only after ST-segment elevation myocardial infarction - Weng, Hong; Zhang, Zhen-Jian; Zeng, Xian-Tao (Journal of Thoracic Disease, 2016)
We read with great interest the recently published article written by Anantha Narayanan et al. (1) entitled ‘What is the optimal approach to a non-culprit stenosis after ST-elevation myocardial infarction - Conservative therapy or upfront revascularization? An updated meta-analysis of randomized trials’.